2021
DOI: 10.2147/jbm.s294958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hematological Parameters of Helicobacter pylori-Infected Adult Patients at Southern Ethiopia: A Comparative Cross-Sectional Study

Abstract: Background Helicobacter pylori ( H. pylori ) infection is a global public health problem, a higher burden of the infection was reported in developing countries including Ethiopia. It has been associated with several gastrointestinal diseases, and recently implicated in some hematological abnormalities. Despite the high prevalence of H. pylori infection in Ethiopia, there was limited data regarding the relationship between hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Likewise, Helicobacter pylori (H. pylori) infection is a global public health problem [34], with higher burdens in the developing nations [34,35], mostly owing to low socio-economic levels, and the potential drinking of contaminated water. H. pylori infection is very common with a mean global prevalence of 58%, partly due to immigrants coming from countries with a high prevalence of H. pylori infection [36].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Helicobacter pylori (H. pylori) infection is a global public health problem [34], with higher burdens in the developing nations [34,35], mostly owing to low socio-economic levels, and the potential drinking of contaminated water. H. pylori infection is very common with a mean global prevalence of 58%, partly due to immigrants coming from countries with a high prevalence of H. pylori infection [36].…”
Section: Introductionmentioning
confidence: 99%
“…Such triggers may include but are not limited to certain infections that may be conducive to anemia of inflammation and elevated RDW (e.g. H. pylori infection) (Haile and Timerga, 2021). In fact, H. pylori infection is more prevalent and can lead to atrophic gastritis to a greater extent among men than among women (Ferro et al, 2019) and was shown recently to be associated with incident AD mostly among men (Beydoun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori (H pylori ) infection was a global public health problem, with higher burdens in the developing countries. [ 1 , 2 ] Nevertheless, epidemiological researches in China yielded inconsistent conclusion. [ 3 ] At the same time, the prevalence of H pylori infection in China might be diverse among different ethnics and different regions.…”
Section: Introductionmentioning
confidence: 99%